Acionamento de dois sistemas de bombeamento alimentados por uma central de microgeração fotovoltaica - Vicentin, Tiago Aparecido [UNESP] (2014)
To evaluate the performance of pumps powered by a photovoltaic microgeneration (MGD-FV), it was necessary to mount a system of monitoring and data collection of production and consumption of energy, these data needed for specific indices that would determine the pumping capacity of two separate hydraulic pumps, installed in the Site Model Farm Lageado, bringing water from a tanker to a storage tank. The performance of each pump was assessed in terms of their electrical and hydraulic characteristics and their interaction with the solar irradiance available for your drive. Each system worked into three booster gauge pressures during 5 days. The volume of water pumped by the two proposed systems ranged between 5244-9398 liters / day for the PV pumping system - SBF2 and 6249-7792 liters / day for the PV pumping system - SBF1, both of which have pumped enough water to meet the basic needs of a small farm. The practical performance of each system was checked as a function of (IB) pumping rate in l / kWh and (IC) rate of consumption in kWh / l, based on these indices may be noted that under the conditions of this experiment the pump SBF2 is the most suitable for gauge height values between 2.5 and 7.5 mca in regions with low levels of irradiation or the seasons which have reduced energy available in the period, it has greater volume pumped when subjected to these working conditions. The SBF1 pump is most suitable for gauge height values between 7.5 and 13.5 mca in regions with high irradiation